UJI PRODUKSI BIOSURFAKTAN OLEH Pseudomonas sp. PADA SUBSTRAT YANG BERBEDA - Fatimah (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2007)
Biosurfactant, microbial metabolite whose properties like surfactant, was suggested to replace chemically synthesized surfactant for take in hand environtmental pollution by petroleum hydrocarbon. This work was done to examine potency of Pseudomonas sp. isolated from Tanjung Perak Harbor to produce biosurfactant. Also, to know the effect of different substrates (glucose + yeast extract, lubricating oil and hexadecane) toward biosurfactant production. Pseudomonas sp. grown in mineral synthetic water and biosurfactant production was measured on stationary phase. Biosurfactant production based on emulsification activity and surface tension reduction of supernatant (using Du Nouy tensiometer). Solar, lubricating oil, and hexadecane were used to examine emulsification activity. Results indicated that Pseudomonas sp. have a potency to produce biosurfactant. Surface tension of supernatant decreased up to 20 dyne/cm, when grown on hexadecane substrate. Hexadecane is the best growing substrate for biosurfactant production than others.